Programa Ler e Escrever e o processo de escolarização do aluno com deficiência intelectual no ensino fundamental - Simioni, Sônia Maria Rodrigues (2016)
The Reading and Writing Program was implemented at state public as a public policy with specific goals: accelerating the literacy process; reverse the academic failure of students without reading and writing appropriation at the end of the cycle I; distribute educational materials in schools; and provide network training for teachers to implement the Program. This study aimed to understand possible contributions to the process of education of students with Intellectual Disabilities in the teaching perspective. The qualitative research was based on the interpretation of text and themes for data analysis, held at a public school in a medium-sized city from São Paulo state. Three teachers of common classroom and four students with Intellectual Disability / Down Syndrome participated of this. The instruments were: field diary; Probing; Class Weekly Routine; questionnaire for the participating teachers. The intervention was done in the classroom in two semesters. The results of the document analysis showed that the Reading and Writing Program Guides direct for an activity in the classroom that does not consider students with Intellectual Disabilities, with extreme learning difficulties and with a lag. The questionnaire responses showed that the teachers believe that the Program does not meet the students with Intellectual Disabilities, pointing out the need for previous training and then serve them; lack of teacher training courses to meet the student with Intellectual Disabilities in the inclusive perspective, that would be relevant item. Observations during the intervention showed that: the teachers believed these students could not learn because of the disciplinary aspect caused by intellectual disadvantage; the class routine does not allow for individualized care and; need for an expert professional in the classroom. The Reading and Writing Program uses as one of its instruments the survey, which does not offer a true picture of the classroom; it does not help in the resumption of teacher actions to mediate learning, and therefore, does not generate progress of students who do not reach the alphabetic hypothesis; It does not contribute to the inference of alphabetic level of the student by the teacher, who goes for it of his own criteria. The adapted activities from the Weekly Routine indicate that the Reading and Writing Program contributes to creating an inclusive environment in the classroom, but not enough to promote advances in the acquisition of reading and writing in students with Intellectual Disabilities. The education of students with Intellectual Disabilities, in the public school of São Paulo state, does not meet the legal requirements and propagates a school culture of exclusion.